ANALISIS PERSEBARAN LAMUN MENGGUNAKAN TEKNIK PENGINDERAAN JAUH DI PULAU SAPUDI, KABUPATEN SUMENEP - Mardyana Riswati; Makhfud Efendy (Department of Marine and Fisheries, Trunojoyo University of Madura, Indonesia, 2020)
ABSTRACTSapudi Island in Sumenep Regency has a fairly complete ecosystem including mangrove ecosystems, seagrass ecosystems, and coral reef ecosystems. Seagrass ecosystems are ecosystems that have a very important role for waters. The purpose of this study was to determine changes in the extent of seagrass beds and the causes of the increase or decrease in changes in seagrass beds in Sapudi Island, Sumenep Regency. In the results of the study, the area of seagrass in September decreased by -0.145 Ha with a rate of change of -1.44%. Factors causing a decrease in the area of seagrasses are currents that move from the south towards the island of Java and the Bali Strait which causes seeds from seagrasses to move from one location to a new location. In addition, sea surface temperature in 2014 was not optimal for seagrass development while in 2018 it was considered optimal for seagrass development. So that the seagrass ecosystem experienced changes in area. The highest percentage of seagrass closure on Sapudi Island is station 4 with a percentage value of 95.9% and the lowest percentage value is station 1 with a percentage value of 1%. Seagrass distribution patterns at stations 1, 2, and 3 are uniform. Whereas station 4 is classified as a group. The quality of the waters on Sapudi Island is reasonable for the survival of seagrass on Sapudi Island.Keyword: Imagery Satelitte, Seagrass, Sapudi IslandABSTRAKPulau Sapudi di Kabupaten Sumenep mempunyai ekosistem yang cukup lengkap diantaranya terdapat ekosistem mangrove, ekosistem lamun, dan ekosistem terumbu karang. Ekosistem lamun merupakan ekosistem yang mempunyai peranan yang sangat penting bagi perairan. Tujuan pada penelitian ini untuk mengetahui perubahan luasan padang lamun dan faktor penyebab bertambahnya atau berkurangnya perubahan luasan padang lamun di Pulau Sapudi, Kabupaten Sumenep. Pada hasil penelitian, luasan pada padang lamun di bulan September mengalami penurunan luasan sebesar -0,145 Ha dengan laju perubahan lusan -1,44%. Faktor yang menyebabkan terjadinya penurunan luasan pada lamun adalah arus yang bergerak dari arah selatan menuju ke Pulau Jawa dan Selat Bali yang mengakibatkan benih dari lamun berpindah dari satu lokasi ke lokasi yang baru. Selain itu pada suhu permukaan laut pada tahun 2014 tidak optimal untuk perkembangan lamun sedangkan pada tahun 2018 termasuk optimal untuk perkembangan lamun. Sehingga ekosistem lamun mengalami perubahan luasan. Persentase penutupan lamun di Pulau Sapudi tertinggi terletak pada stasiun 4 dengan nilai persentase 95,9% dan nilai persentase terendah terletak pada stasiun 1 dengan nilai persentase 1%.Pola sebaran lamun pada stasiun 1, 2, dan 3 termasuk golongan seragam. Sedangkan pada stasiun 4 tergolong mengelompok. Kualitas perairan di Pulau Sapudi tergolong layak untuk kelangsungan hidup bagi lamun di Pulau Sapudi.Kata kunci: Citra Satelit, Lamun, Pulau Sapudi